2021
DOI: 10.3389/fcvm.2021.650374
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0068087 Silencing Ameliorates Oxidized Low-Density Lipoprotein-Induced Dysfunction in Vascular Endothelial Cells Depending on miR-186-5p-Mediated Regulation of Roundabout Guidance Receptor 1

Abstract: Background: Circular RNAs (circRNAs) are endogenous non-coding RNAs involved in the progression of atherosclerosis (AS). We investigated the role of circ_0068087 in AS progression and its associated mechanism.Methods: The 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide (MTT) assay, flow cytometry, and enzyme-linked immunosorbent assay (ELISA) were performed to analyze the viability, apoptosis, and inflammatory response of HUVECs, respectively. Reverse transcription-quantitative polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 39 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…Serving as the sponge of miR-876-3p, the Circ_0093887 has also been reported to help protect HAECs against the oxLDL-induced inflammatory and apoptotic damages ( 39 ). Furthermore, for the circ_0068087, with similar targeted ROBO1 expression in circ-USP36, it not only aggravates hyperglycemia-induced dysfunction and inflammation of ECs with a sponge of miR-197 in diabetes but also alleviated oxLDL-induced dysfunction in HUVECs partly accompanied by reducing and upregulating miR-186-5p ( 42 ).…”
Section: Oxldl and Endothelial Cell Dysfunctionmentioning
confidence: 99%
“…Serving as the sponge of miR-876-3p, the Circ_0093887 has also been reported to help protect HAECs against the oxLDL-induced inflammatory and apoptotic damages ( 39 ). Furthermore, for the circ_0068087, with similar targeted ROBO1 expression in circ-USP36, it not only aggravates hyperglycemia-induced dysfunction and inflammation of ECs with a sponge of miR-197 in diabetes but also alleviated oxLDL-induced dysfunction in HUVECs partly accompanied by reducing and upregulating miR-186-5p ( 42 ).…”
Section: Oxldl and Endothelial Cell Dysfunctionmentioning
confidence: 99%
“…In addition, Zhang et al declared that SNHG7 sponged miR-186-5p to modulate endothelial cells’ phenotype [ 20 ]. More importantly, Li et al suggested that miR-186-5p exerted a protective role by downregulating ROBO1 in ox-LDL-exposed human umbilical vein endothelial cells [ 39 ]. Nevertheless, the function of miR-186-5p in CAD is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The circ_0068087 expression level was increased in blood sample from patients with T2D. Circ_0068087 knockdown could ameliorate ox-LDL-induced HUVEC dysfunction by miR-186-5p and roundabout guidance receptor 1 (ROBO1) ( Li et al, 2021a ). Moreover, circ_0068087 knockdown could also suppress cell dysfunction under HG conditions.…”
Section: Vascular Damage Due To Hyperglycemia and Dyslipidemiamentioning
confidence: 99%